Taliban insurgency and transnational organized crime nexus - Mohammad Ayub Mirdad (Masyarakat, Kebudayaan dan Politik, 2020)
Afghanistan has been demolished by more than three decades of the ongoing war since the war against the Soviet Union started in 1979. The Afghanistan-Pakistan region provides a geographically secure location and a space of opportunity for organized crime and terrorist groups. This paper aims at exploring the Taliban nexus with organized crime groups in Afghanistan and the region through Makarenko’s crime-terror continuum theory. The method of this study is qualitative through the descriptive-analytical approach. The growing connection between insurgents and organized crime poses essential challenges to the region. Each group has developed both criminal and terrorist elements while not relinquishing its original organizing principle. Afghanistan is a war-torn country and weak governance, terrorism, narcotics, illegal mining, poor border control, and widespread corruption provide the perfect opportunity for convergence of the Taliban with organized criminal and insurgent groups in the region. The Taliban and organized crime groups are involved in kidnapping for ransom, drug trade, extortion, and exploitation of natural resources. The finding indicates that, although the objectives of the insurgent and organized crime organizations differ widely, these enabling variables are also suitable for organized crime organizations. The primary objective of organized crime is to gain profit, and the objective of the insurgent is to contest the state power and promote political change through violence. The economic sources are the primary main reason why the two organizations converge.